2017
DOI: 10.1589/jpts.29.713
|View full text |Cite
|
Sign up to set email alerts
|

Effects of taekwondo intervention on cognitive function and academic self-efficacy in children

Abstract: [Purpose] The purpose of this study was to investigate the effects of taekwondo training on cognitive function and academic self-efficacy in children. [Subjects and Methods] Thirty-five children participated in the study. Seventeen children were randomly selected to undergo taekwondo training for 16 weeks (5 times per week). As controls, 18 children received no training. Cognitive function and academic self-efficacy were measured using the Stroop Color and Word Test (Word, Color, and Color-Word) and academic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…The entrepreneurial traits possessed by individuals are closely related to their psychological behaviors ( O’Shea et al, 2017 ). To analyze entrepreneurship education from a psychological perspective, the element of entrepreneurial self-efficacy is an important embodiment of personality psychological traits, both in terms of tasks and fields ( Cho et al, 2017 ). From the perspective of ethics, it is meaningful to analyze and explore the self-employment behavior of college students.…”
Section: Introductionmentioning
confidence: 99%
“…The entrepreneurial traits possessed by individuals are closely related to their psychological behaviors ( O’Shea et al, 2017 ). To analyze entrepreneurship education from a psychological perspective, the element of entrepreneurial self-efficacy is an important embodiment of personality psychological traits, both in terms of tasks and fields ( Cho et al, 2017 ). From the perspective of ethics, it is meaningful to analyze and explore the self-employment behavior of college students.…”
Section: Introductionmentioning
confidence: 99%
“…While the practice of martial arts effectively improves various areas of physical fitness, favorable outcomes extend to discipline and character growth (Lakes & Hoyt, 2004). Additionally, martial arts are associated with positive affective benefits, such as higher self-esteem, emotional stability, assertiveness, and self-confidence (Cho, Kim, & Roh, 2017;Weiser, Kutz, Kutz, & Weiser, 1995). Social benefits of martial arts training include learning cope with challenging situations, such as competition and perceptions of disadvantage (Weiser et al, 1995); increased respect; and positive effects on the development of sociability (Finkenberg, 1990;Roh, Cho, & So, 2018).…”
Section: Martial Arts As An Interventionmentioning
confidence: 99%
“…Social benefits of martial arts training include learning cope with challenging situations, such as competition and perceptions of disadvantage (Weiser et al, 1995); increased respect; and positive effects on the development of sociability (Finkenberg, 1990;Roh, Cho, & So, 2018). Finally, martial arts study has cognitive benefits including increased concentration and awareness as well as improved executive function (Cho, Kim, et al, 2017;Lakes et al, 2013).…”
Section: Martial Arts As An Interventionmentioning
confidence: 99%
“…Within this theoretical framework, taekwondo (TKD) is a Korean martial art, refined over generations, that engages students in a range of cognitive, physical, emotional, social and educational processes [11,12,13,14,15,16,17,18,19,20]. Recently, TKD has received attention from scholars and researchers, who have investigated the benefits of TKD training among children and adolescents, in terms of cognitive and behavioral improvements [21,22,23,24]. However, the possible therapeutic implications of TKD practice still remain overlooked in the extant scholarly literature.…”
Section: Introductionmentioning
confidence: 99%
“…Authors showed that school-based TKD training over three months resulted in larger improvements of different functions, including cognitive self-regulation, affective self-regulation, pro-social behavior, classroom conduct, and performance on a mental math test. Cho et al [22] examined the effects of a 4-month TKD intervention in 30 healthy children. The Color-Word test scores were significantly higher in the TKD group than in the control group after the training period.…”
Section: Introductionmentioning
confidence: 99%